Karakteristik Mutu Sensori Dan Kimia Liang Teh Pontianak Kaya Antioksidan Pada Berbagai Suhu Pengeringan - Florentina, Devi Viola; Dewi, Yohana Sutiknyawati Kusuma; Priyono, Suko (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
Liang tea Pontianak is a traditional beverage product made using recipes passed down from generation to generation. Liang tea Pontianak is usually made in the form of fresh drinks however, the liang tea Pontianak drink in the form of a fresh drink does not have a long shelf life. One way to overcome this liang tea Pontianak can be processed into dry liang tea Pontianak. The purpose of this study was to obtain the drying temperature of the liang tea Pontianak formulation which resulted in the sensory and chemical quality characteristics of liang tea Pontianak which was rich in the best antioxidants in dry form. This study used a randomized block design (RAK) with one factor, namely the variation of the drying temperature of liang tea Pontianak burrows which consisted of 3 levels treatment with 9 reolications (50 ± 5, 60 ± 5, 70 ± 5)°C. The data obtained were analyzed using 5%, with further testing using the BNJ Test with a level of 5%. The best treatment was using the effectiveness index test. The results showed that the drying temperature liang tea Pontianak burrows was carried out with the best temperature of 60 ± 5°C. The best sensory test results liang tea Pontianak were color 3,97 (like), aroma 3,53 (like) and taste 3,83 (like) . The best chemical test resulted in liang tea Pontianak in the form of antioxidant activity of 44,64% and total flavonoids 50,18 mg QE/g.Keywords - antioxidant activity, liang-tea Pontianak, drying temperature, Rancangan Acak Kelompok